Controlled drug delivery system by fs-laser micromachined biocompatible rubber latex membranes - Almeida, G. F. B.; Cardoso, M. R.; Zancanela, D. C. [UNESP]; Bernardes, L. L. [UNESP]; Norberto, A. M. Q.; Barros, N. R. [UNESP]; Paulino, C. G. [UNESP]; Chagas, A. L. D. [UNESP]; Herculano, R. D. [UNESP]; Mendonca, C. R. (Elsevier B.V., 2020)
The concept behind drug delivery systems is to provide the correct amount of pharmaceutical compound to a desired body part within a predefined timespan. It can be made of various materials such as liposomes, niosomes, nano/microcapsules, cyclodextrins, polymers and many more. Natural rubber latex is used as solid matrix for drug delivery because it stimulates the healing process of wounds and angiogenesis. In this context, we have produced natural rubber latex membranes with of 2000, 6000 and 10,000 pore/cm(2) via fs-laser micromachining and studied its influence on the drug delivery experiments. Drug release kinetics of Ciprofloxacin-loaded microdrilled biopolymer samples showed that the final concentration of drug released has a linear dependence with the pore density. According to infrared spectroscopy analysis, latex membranes maintained their structural properties after ultrashort pulse irradiation and ciprofloxacin adsorption. The demonstration of a fast and reliable production of a controlled drug delivery system puts fs-laser micromachined porous natural rubber latex as a promising candidate for in vivo application in which a proper amount of drug needs to be released.
Keywords: Drug delivery system; Natural rubber latex; Biomaterials; Femtosecond laser micromachining; Microdrilling; Surface morphology